Asymmetric Hydrogenation with Iridium C, N and N, P Ligand Complexes: Characterization of Dihydride Intermediates with a Coordinated Alkene1. (21st January 2014) - Gruber, Stefan; Pfaltz, Andreas
Abstract Previously elusive iridium dihydride alkene complexes have been identified and characterized by NMR spectroscopy in solution. Reactivity studies demonstrated that these complexes are catalytically competent intermediates. Additional H2 is required to convert the catalyst‐bound alkene into the hydrogenation product, supporting an IrIII/IrV cycle via an [IrIII(H)2(alkene)(H2)(L)]+ intermediate, as originally proposed based on DFT calculations. NMR analyses indicate a reaction pathway proceeding through rapidly equilibrating isomeric dihydride alkene intermediates with a subsequent slow enantioselectivity‐determining step. As in the classical example of asymmetric hydrogenation with rhodium diphosphine catalysts, it is a minor, less stable intermediate that is converted into the major product enantiomer.